2009
DOI: 10.1158/1078-0432.ccr-09-0829
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ–Dependent Infiltration of Human T Cells into Neuroblastoma TumorsIn vivo

Abstract: Purpose: To investigate the impact of interferon-γ-mediated upregulation of major histocompatibility complex class I expression on tumor-specific T-cell cytotoxicity and T-cell trafficking into neuroblastoma tumors in vivo. Experimental Design: Restoration of major histocompatibility complex class I expression by interferon-γ treatment enhances killing of neuroblastoma cells. To understand the potential of this approach in vivo, we developed a novel model of neuroblastoma in which NOD/scid/IL2Rγ null immunodef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
6
22
0
Order By: Relevance
“…Recombinant human interferon-g has been demonstrated to enhance expression of MHC class I molecules and antigen processing components on human neuroblastoma cells, to increase trafficking of human T cells into neuroblastoma tumors in vivo, and to augment the killing of neuroblastoma cells by tumor-specific T cells. 42,43 However, immunotherapeutic use of interferon-g in the treatment of human solid tumors is limited by negative feedback loops preventing long-lasting biological effects. 44,45 Adoptive T-cell therapy using autologous ex vivo-expanded tumor-infiltrating T cells transferred back into patients, represents a fascinating option for adjuvant treatment of patients with aggressive neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human interferon-g has been demonstrated to enhance expression of MHC class I molecules and antigen processing components on human neuroblastoma cells, to increase trafficking of human T cells into neuroblastoma tumors in vivo, and to augment the killing of neuroblastoma cells by tumor-specific T cells. 42,43 However, immunotherapeutic use of interferon-g in the treatment of human solid tumors is limited by negative feedback loops preventing long-lasting biological effects. 44,45 Adoptive T-cell therapy using autologous ex vivo-expanded tumor-infiltrating T cells transferred back into patients, represents a fascinating option for adjuvant treatment of patients with aggressive neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…These include decreased expression of peptide presenting HLA class I molecules by tumor cells, which can impair target peptide recognition by CTLs (25, 3941). Also, neuroblastoma cells express low levels of antigen processing genes, including LMP-2, LMP-7, and TAP-1, which are necessary for preparation of peptides from proteins for presentation by HLA class I molecules to CTLs (42, 43).…”
Section: Cytotoxic T Lymphocytesmentioning
confidence: 99%
“…Previous work from our group and others has demonstrated that exogenous interferon g (IFNg) results in upregulation of MHC Class I on previously MHC Class I-low/negative tumors, and that this upregulation can result in increased T-cell infiltration and enhanced tumor killing in vivo. 39,40 Combining this observation with the robust antitumor activity of the cells described in this study, one could envision a clinical trial design in which high-risk neuroblastoma patients are treated with IFNg surrounding the time of tTCR T-cell infusion to enhance tumor infiltration and antitumor activity. There is also the possibility that not all tumor cells will have undetectable levels of Class I, and some tTCR T cells will be able to engage and activate.…”
Section: Discussionmentioning
confidence: 99%
“…39 This low level of Class I expression has been correlated with a low degree of T-cell infiltration, and thus it has been proposed that reduced MHC expression levels may confer "protection" from cell-mediated immunity in some tumors. In contradistinction, CAR T cells targeting neuroblastoma via an MHC-independent mechanism demonstrate robust tumor infiltration and antitumor responses.…”
Section: Discussionmentioning
confidence: 99%